Psychohistory and Psychopoetics Freudian Roots and Ancient Greek Symbolism - Michael Kuznetsov (Universitas Negeri Semarang, 2025)
What if the grand tapestry of history, traditionally woven by kings and treaties, is instead driven by the subterranean currents of unconscious desires and childhood traumas? This article probes these hidden forces through the interdisciplinary frameworks of psychohistory and psychopoetics, offering a provocative reimagining of human agency and cultural evolution. The inquiry commences with a rigorous psychoanalytic examination of Sigmund Freud and Ludwig Jekels’ 1914 study, Der Wendepunkt im Leben Napoleons I, which dissects Napoleon Bonaparte’s meteoric rise through the lens of early familial dynamics and paraphilic tendencies—ranging from voyeurism to sadomasochism—rooted in his idolization of Pasquale Paoli. This seminal work prefigured psychohistory, formalized by Erik Erikson in 1958, as a method to unravel history as the enactment of repressed psychic conflicts and collective fantasies, challenging conventional historiography. The exploration deepens with an incisive analysis of Greek mythology’s primordial narratives, where the androgynous Aether begets Uranus and Gaia, initiating a cosmic drama of castration and rebellion. This foundational mythos crystallizes the Oedipus and Electra complexes, establishing archetypal psychic structures that underpin Western identity and patriarchal ascendancy. Turning to psychopoetics, this study decodes the symbolic lexicon of ancient Greek culture, interrogating how color gradations—blue for divine allegiance, red for martial fervor, green for sensual rebirth—embody unconscious fears and aspirations. Study propose an innovative expansion of psychopoetics, integrating color semiotics with genetic, economic, and linguistic determinants, to illuminate the phylogenetic imprint of civilizations. This approach not only redefines cultural analysis but also underscores the irreversible trajectory of history, shaped by the magnetic influence of visionary leaders and the enduring hypnosis of mass psychology.